Network analysis of postpartum depression symptoms and perinatal risk factors in Chinese women: a prospective observational study - Zhang, Xian; Yao, Jiasi; He, Hongxiao; Li, Jiahe; Li, Junying; Lu, Hong; Huang, Xiaona; Tian, Xiaobo; Liang, Junxiao; Gong, Luxia; Pang, Ruyan; Luo, Qiong; et al. (Frontiers in Psychology, 2025)
BackgroundPostpartum depression (PPD) is a prevalent mental health issue with significant implications for maternal and infant wellbeing. Despite extensive research, the complex interplay of perinatal factors contributing to PPD remains inadequately characterized. This study utilizes a network analysis approach to identify central depressive symptoms, critical perinatal risk factors, and pathways contributing to PPD among Chinese postpartum women.MethodsA prospective observational study enrolled 377 women from 10 tertiary hospitals in China. Sociodemographic and perinatal factors were assessed shortly after childbirth. At 4–6 weeks postpartum, PPD symptoms were evaluated using the Edinburgh Postnatal Depression Scale (EPDS). Maternal and infant health outcomes, breastfeeding experiences, and family support were captured through self-administered questionnaires. Random forest and Bayesian network analyses were employed to identify influential factors and their interrelationships.ResultsAmong the participants, 98 women (26.0, 95% CI: 21.6–30.7%) screened positive for PPD (EPDS score ≥10). Anxiety/Worry emerged as the most central symptom in the network, with the highest strength and centrality (Degree = 0.893, Betweenness = 0.888). Key risk factors included breastfeeding challenges (RF = 0.752), maternal physical complaints (RF = 0.431), and adverse infant health conditions (RF = 0.350). Protective effects were observed for prolonged skin-to-skin contact, family support for breastfeeding, and positive childbirth self-perception. Hospital type served as a central bridging node within the network, strongly connected with factors related to peripartum care services, childbirth experience and PPD.ConclusionThis study reveals a significant prevalence of PPD among mothers in China. It underscores the positive impact of skin-to-skin contact, continuous postpartum care and tailored breastfeeding support in addressing PPD. These findings will advance PPD prevention strategies and inform evidence-based clinical practice in postpartum care.